2019
DOI: 10.3389/fonc.2019.01128
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Controversial Issues in the Management of Head and Neck Cancer: A Swiss Multidisciplinary and Multi-Institutional Patterns of Care Study—Part 4 (Biomarkers)

Abstract: Background: The Head and Neck Cancer Working Group of Swiss Group for Clinical Cancer Research (SAKK) has investigated the level of consensus (LOC) and discrepancy in everyday practice of diagnosis and treatment in head and neck cancer.Materials and Methods: An online survey was iteratively generated with 10 Swiss university and teaching hospitals. LOC below 50% was defined as no agreement, while higher LOC were arbitrarily categorized as low (51–74%), moderate (75–84%), and high (≥85%).Results: Any LOC was ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…These results point to the possibility of MTV being able to help decide between treatments, and it might even throw some light into the existing controversies in HNC treatment strategy selection. 4,5 Many prospective and multicentric trials are still required to consider modifying the standardized protocols for managing patients with HNC. Nevertheless, and with all due limitations, pretreatment MTV and TLG offer valuable information that can aid in selecting patients who would benefit from a more thorough follow up for early recurrence detection and, perhaps in the future, may also aid in treatment strategy selection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results point to the possibility of MTV being able to help decide between treatments, and it might even throw some light into the existing controversies in HNC treatment strategy selection. 4,5 Many prospective and multicentric trials are still required to consider modifying the standardized protocols for managing patients with HNC. Nevertheless, and with all due limitations, pretreatment MTV and TLG offer valuable information that can aid in selecting patients who would benefit from a more thorough follow up for early recurrence detection and, perhaps in the future, may also aid in treatment strategy selection.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Nonetheless its relevance, there are still many controversies and discrepancies among practitioners surrounding the therapeutic approaches for these patients, especially in locally advanced HNC. [3][4][5] The two main tools to categorize patients with HNC and to assess treatment and prognosis are the Union Internationale Contre le Cancer (UICC) TNM classification and the American Joint…”
mentioning
confidence: 99%
“…The Swiss multi-institutional patterns of care study by Elcin et al reported that about 80% of centres consented favouring the SIB technique over other techniques for planning. 19 Conventionally, sequential IMRT follows a non-segmented way of contouring the target volume in which low/intermediate-risk PTV includes the high-risk PTV, whereas, in SIB, both segmented and non-segmented target volumes with regard to low-risk PTV can be considered for planning. Although there is no clinical evidence on improved outcome from either, the disadvantage of using sequential IMRT includes longer planning time and the need for summation of different treatment plans.…”
Section: Discussionmentioning
confidence: 99%
“…It was accepted by the current edition of the Classification of Head and Neck Tumors but with the mention that grading alone does not correlate well with prognosis [15]. It is not a part of the UICC staging system, but some data consider high grade as an indication for the adjuvant treatment in OSCC [16,17].…”
Section: The Conventional Histopathological Diagnostic and Morphologimentioning
confidence: 99%